Multiple Pyarthrosis in Human Immunodeficiency Virus-Infected Hemophiliacs - Alistair Ingram; Martin J Inwood; Dan Gregson; Michael Coppolino (Canadian Journal of Infectious Diseases)
Classically, a swollen, painful joint in a patient with hemophilia has been considered to be due to a hemarthrosis until otherwise proven, and treated immediately with appropriate coagulation factor replacement. Two cases of human immunodeficiency virus (hiv)-infected hemophiliacs presenting with an initial apparent hemarthrosis, complicated subsequently by numerous pyarthroses and sepsis are described. In light of the prevalence of hiv infection in the adult hemophiliac population with arthropathy, a reappraisal of the clinical caveat of immediate infusion without joint aspiration is required.